Identification of Sodium Transients Through NaV1.5 Channels as Regulators of Differentiation in Immortalized Dorsal Root Ganglia Neurons - Martínez, Antón L.; Brea, José; Domínguez, Eduardo; Varela, María J.; Allegue, Catarina; Cruz, Raquel; Monroy, Xavier; Merlos, Manuel; Burgueño, Javier; Carracedo, Ángel; Loza, María Isabel (Frontiers in Cellular Neuroscience, 2022)
Neuronal differentiation is a complex process through which newborn neurons acquire the morphology of mature neurons and become excitable. We employed a combination of functional and transcriptomic approaches to deconvolute and identify key regulators of the differentiation process of a DRG neuron-derived cell line, and we focused our study on the NaV1.5 ion channel (encoded by Scn5a) as a channel involved in the acquisition of DRG neuronal features. Overexpression of Scn5a enhances the acquisition of neuronal phenotypic features and increases the KCl-elicited hyperexcitability response in a DRG-derived cell line. Moreover, pharmacologic inhibition of the NaV1.5 channel during differentiation hinders the acquisition of phenotypic features of neuronal cells and the hyperexcitability increase in response to changes in the extracellular medium ionic composition. Taken together, these data highlight the relevance of sodium transients in regulating the neuronal differentiation process in a DRG neuron-derived cell line.